HUBUNGAN ANTARA JIWA DAN REINKARNASI DALAM AGAMA HINDU: english - Maulana, Abdullah Muslich Rizal; Syifa, Himmah Nabilah; Hartanto, Kharisa Aura; Hidayatika, Malika Shafari; Rahma, Maharani Zweida (UHN IGB Sugriwa Denpasar, 2023)
Panca Sradha is a belief for Hindus that must be firmly entrenched in the hearts of Hindus in order to achieve the goal of life in the world. Reincarnation according to the teachings of Hinduism is included in the Panca Sradha beliefs, which must be believed by Hindus. The process of reincarnation is a unique and abstract phenomenon that requires knowledge to understand it and research it. Many figures have succeeded in researching the process of reincarnation. In fact, reincarnation exists and is the result of actions committed while living in the world, if a person does good during his lifetime then he is reborn in the same or better form. also with karma. Reincarnation will continue to occur to a person until the spirit reaches a perfect and eternal point, this place is known as moksha. The process of reincarnation often occurs when a person is reborn in a different form but in the same atma/soul.